summary |
shortlog |
changelog |
graph |
tags |
bookmarks |
branches |
files |
changeset |
file |
latest |
revisions |
annotate |
diff |
comparison |
raw |
help

src/HOL/Unix/Nested_Environment.thy

author | wenzelm |

Sat, 07 Apr 2012 16:41:59 +0200 | |

changeset 47389 | e8552cba702d |

parent 44703 | f2bfe19239bc |

child 49679 | 835d55b4fc8c |

permissions | -rw-r--r-- |

explicit checks stable_finished_theory/stable_command allow parallel asynchronous command transactions;
tuned;

(* Title: HOL/Unix/Nested_Environment.thy Author: Markus Wenzel, TU Muenchen *) header {* Nested environments *} theory Nested_Environment imports Main begin text {* Consider a partial function @{term [source] "e :: 'a \<Rightarrow> 'b option"}; this may be understood as an \emph{environment} mapping indexes @{typ 'a} to optional entry values @{typ 'b} (cf.\ the basic theory @{text Map} of Isabelle/HOL). This basic idea is easily generalized to that of a \emph{nested environment}, where entries may be either basic values or again proper environments. Then each entry is accessed by a \emph{path}, i.e.\ a list of indexes leading to its position within the structure. *} datatype ('a, 'b, 'c) env = Val 'a | Env 'b "'c \<Rightarrow> ('a, 'b, 'c) env option" text {* \medskip In the type @{typ "('a, 'b, 'c) env"} the parameter @{typ 'a} refers to basic values (occurring in terminal positions), type @{typ 'b} to values associated with proper (inner) environments, and type @{typ 'c} with the index type for branching. Note that there is no restriction on any of these types. In particular, arbitrary branching may yield rather large (transfinite) tree structures. *} subsection {* The lookup operation *} text {* Lookup in nested environments works by following a given path of index elements, leading to an optional result (a terminal value or nested environment). A \emph{defined position} within a nested environment is one where @{term lookup} at its path does not yield @{term None}. *} primrec lookup :: "('a, 'b, 'c) env \<Rightarrow> 'c list \<Rightarrow> ('a, 'b, 'c) env option" and lookup_option :: "('a, 'b, 'c) env option \<Rightarrow> 'c list \<Rightarrow> ('a, 'b, 'c) env option" where "lookup (Val a) xs = (if xs = [] then Some (Val a) else None)" | "lookup (Env b es) xs = (case xs of [] \<Rightarrow> Some (Env b es) | y # ys \<Rightarrow> lookup_option (es y) ys)" | "lookup_option None xs = None" | "lookup_option (Some e) xs = lookup e xs" hide_const lookup_option text {* \medskip The characteristic cases of @{term lookup} are expressed by the following equalities. *} theorem lookup_nil: "lookup e [] = Some e" by (cases e) simp_all theorem lookup_val_cons: "lookup (Val a) (x # xs) = None" by simp theorem lookup_env_cons: "lookup (Env b es) (x # xs) = (case es x of None \<Rightarrow> None | Some e \<Rightarrow> lookup e xs)" by (cases "es x") simp_all lemmas lookup_lookup_option.simps [simp del] and lookup_simps [simp] = lookup_nil lookup_val_cons lookup_env_cons theorem lookup_eq: "lookup env xs = (case xs of [] \<Rightarrow> Some env | x # xs \<Rightarrow> (case env of Val a \<Rightarrow> None | Env b es \<Rightarrow> (case es x of None \<Rightarrow> None | Some e \<Rightarrow> lookup e xs)))" by (simp split: list.split env.split) text {* \medskip Displaced @{term lookup} operations, relative to a certain base path prefix, may be reduced as follows. There are two cases, depending whether the environment actually extends far enough to follow the base path. *} theorem lookup_append_none: assumes "lookup env xs = None" shows "lookup env (xs @ ys) = None" using assms proof (induct xs arbitrary: env) case Nil then have False by simp then show ?case .. next case (Cons x xs) show ?case proof (cases env) case Val then show ?thesis by simp next case (Env b es) show ?thesis proof (cases "es x") case None with Env show ?thesis by simp next case (Some e) note es = `es x = Some e` show ?thesis proof (cases "lookup e xs") case None then have "lookup e (xs @ ys) = None" by (rule Cons.hyps) with Env Some show ?thesis by simp next case Some with Env es have False using Cons.prems by simp then show ?thesis .. qed qed qed qed theorem lookup_append_some: assumes "lookup env xs = Some e" shows "lookup env (xs @ ys) = lookup e ys" using assms proof (induct xs arbitrary: env e) case Nil then have "env = e" by simp then show "lookup env ([] @ ys) = lookup e ys" by simp next case (Cons x xs) note asm = `lookup env (x # xs) = Some e` show "lookup env ((x # xs) @ ys) = lookup e ys" proof (cases env) case (Val a) with asm have False by simp then show ?thesis .. next case (Env b es) show ?thesis proof (cases "es x") case None with asm Env have False by simp then show ?thesis .. next case (Some e') note es = `es x = Some e'` show ?thesis proof (cases "lookup e' xs") case None with asm Env es have False by simp then show ?thesis .. next case Some with asm Env es have "lookup e' xs = Some e" by simp then have "lookup e' (xs @ ys) = lookup e ys" by (rule Cons.hyps) with Env es show ?thesis by simp qed qed qed qed text {* \medskip Successful @{term lookup} deeper down an environment structure means we are able to peek further up as well. Note that this is basically just the contrapositive statement of @{thm [source] lookup_append_none} above. *} theorem lookup_some_append: assumes "lookup env (xs @ ys) = Some e" shows "\<exists>e. lookup env xs = Some e" proof - from assms have "lookup env (xs @ ys) \<noteq> None" by simp then have "lookup env xs \<noteq> None" by (rule contrapos_nn) (simp only: lookup_append_none) then show ?thesis by (simp) qed text {* The subsequent statement describes in more detail how a successful @{term lookup} with a non-empty path results in a certain situation at any upper position. *} theorem lookup_some_upper: assumes "lookup env (xs @ y # ys) = Some e" shows "\<exists>b' es' env'. lookup env xs = Some (Env b' es') \<and> es' y = Some env' \<and> lookup env' ys = Some e" using assms proof (induct xs arbitrary: env e) case Nil from Nil.prems have "lookup env (y # ys) = Some e" by simp then obtain b' es' env' where env: "env = Env b' es'" and es': "es' y = Some env'" and look': "lookup env' ys = Some e" by (auto simp add: lookup_eq split: option.splits env.splits) from env have "lookup env [] = Some (Env b' es')" by simp with es' look' show ?case by blast next case (Cons x xs) from Cons.prems obtain b' es' env' where env: "env = Env b' es'" and es': "es' x = Some env'" and look': "lookup env' (xs @ y # ys) = Some e" by (auto simp add: lookup_eq split: option.splits env.splits) from Cons.hyps [OF look'] obtain b'' es'' env'' where upper': "lookup env' xs = Some (Env b'' es'')" and es'': "es'' y = Some env''" and look'': "lookup env'' ys = Some e" by blast from env es' upper' have "lookup env (x # xs) = Some (Env b'' es'')" by simp with es'' look'' show ?case by blast qed subsection {* The update operation *} text {* Update at a certain position in a nested environment may either delete an existing entry, or overwrite an existing one. Note that update at undefined positions is simple absorbed, i.e.\ the environment is left unchanged. *} primrec update :: "'c list \<Rightarrow> ('a, 'b, 'c) env option \<Rightarrow> ('a, 'b, 'c) env \<Rightarrow> ('a, 'b, 'c) env" and update_option :: "'c list \<Rightarrow> ('a, 'b, 'c) env option \<Rightarrow> ('a, 'b, 'c) env option \<Rightarrow> ('a, 'b, 'c) env option" where "update xs opt (Val a) = (if xs = [] then (case opt of None \<Rightarrow> Val a | Some e \<Rightarrow> e) else Val a)" | "update xs opt (Env b es) = (case xs of [] \<Rightarrow> (case opt of None \<Rightarrow> Env b es | Some e \<Rightarrow> e) | y # ys \<Rightarrow> Env b (es (y := update_option ys opt (es y))))" | "update_option xs opt None = (if xs = [] then opt else None)" | "update_option xs opt (Some e) = (if xs = [] then opt else Some (update xs opt e))" hide_const update_option text {* \medskip The characteristic cases of @{term update} are expressed by the following equalities. *} theorem update_nil_none: "update [] None env = env" by (cases env) simp_all theorem update_nil_some: "update [] (Some e) env = e" by (cases env) simp_all theorem update_cons_val: "update (x # xs) opt (Val a) = Val a" by simp theorem update_cons_nil_env: "update [x] opt (Env b es) = Env b (es (x := opt))" by (cases "es x") simp_all theorem update_cons_cons_env: "update (x # y # ys) opt (Env b es) = Env b (es (x := (case es x of None \<Rightarrow> None | Some e \<Rightarrow> Some (update (y # ys) opt e))))" by (cases "es x") simp_all lemmas update_update_option.simps [simp del] and update_simps [simp] = update_nil_none update_nil_some update_cons_val update_cons_nil_env update_cons_cons_env lemma update_eq: "update xs opt env = (case xs of [] \<Rightarrow> (case opt of None \<Rightarrow> env | Some e \<Rightarrow> e) | x # xs \<Rightarrow> (case env of Val a \<Rightarrow> Val a | Env b es \<Rightarrow> (case xs of [] \<Rightarrow> Env b (es (x := opt)) | y # ys \<Rightarrow> Env b (es (x := (case es x of None \<Rightarrow> None | Some e \<Rightarrow> Some (update (y # ys) opt e)))))))" by (simp split: list.split env.split option.split) text {* \medskip The most basic correspondence of @{term lookup} and @{term update} states that after @{term update} at a defined position, subsequent @{term lookup} operations would yield the new value. *} theorem lookup_update_some: assumes "lookup env xs = Some e" shows "lookup (update xs (Some env') env) xs = Some env'" using assms proof (induct xs arbitrary: env e) case Nil then have "env = e" by simp then show ?case by simp next case (Cons x xs) note hyp = Cons.hyps and asm = `lookup env (x # xs) = Some e` show ?case proof (cases env) case (Val a) with asm have False by simp then show ?thesis .. next case (Env b es) show ?thesis proof (cases "es x") case None with asm Env have False by simp then show ?thesis .. next case (Some e') note es = `es x = Some e'` show ?thesis proof (cases xs) case Nil with Env show ?thesis by simp next case (Cons x' xs') from asm Env es have "lookup e' xs = Some e" by simp then have "lookup (update xs (Some env') e') xs = Some env'" by (rule hyp) with Env es Cons show ?thesis by simp qed qed qed qed text {* \medskip The properties of displaced @{term update} operations are analogous to those of @{term lookup} above. There are two cases: below an undefined position @{term update} is absorbed altogether, and below a defined positions @{term update} affects subsequent @{term lookup} operations in the obvious way. *} theorem update_append_none: assumes "lookup env xs = None" shows "update (xs @ y # ys) opt env = env" using assms proof (induct xs arbitrary: env) case Nil then have False by simp then show ?case .. next case (Cons x xs) note hyp = Cons.hyps and asm = `lookup env (x # xs) = None` show "update ((x # xs) @ y # ys) opt env = env" proof (cases env) case (Val a) then show ?thesis by simp next case (Env b es) show ?thesis proof (cases "es x") case None note es = `es x = None` show ?thesis by (cases xs) (simp_all add: es Env fun_upd_idem_iff) next case (Some e) note es = `es x = Some e` show ?thesis proof (cases xs) case Nil with asm Env Some have False by simp then show ?thesis .. next case (Cons x' xs') from asm Env es have "lookup e xs = None" by simp then have "update (xs @ y # ys) opt e = e" by (rule hyp) with Env es Cons show "update ((x # xs) @ y # ys) opt env = env" by (simp add: fun_upd_idem_iff) qed qed qed qed theorem update_append_some: assumes "lookup env xs = Some e" shows "lookup (update (xs @ y # ys) opt env) xs = Some (update (y # ys) opt e)" using assms proof (induct xs arbitrary: env e) case Nil then have "env = e" by simp then show ?case by simp next case (Cons x xs) note hyp = Cons.hyps and asm = `lookup env (x # xs) = Some e` show "lookup (update ((x # xs) @ y # ys) opt env) (x # xs) = Some (update (y # ys) opt e)" proof (cases env) case (Val a) with asm have False by simp then show ?thesis .. next case (Env b es) show ?thesis proof (cases "es x") case None with asm Env have False by simp then show ?thesis .. next case (Some e') note es = `es x = Some e'` show ?thesis proof (cases xs) case Nil with asm Env es have "e = e'" by simp with Env es Nil show ?thesis by simp next case (Cons x' xs') from asm Env es have "lookup e' xs = Some e" by simp then have "lookup (update (xs @ y # ys) opt e') xs = Some (update (y # ys) opt e)" by (rule hyp) with Env es Cons show ?thesis by simp qed qed qed qed text {* \medskip Apparently, @{term update} does not affect the result of subsequent @{term lookup} operations at independent positions, i.e.\ in case that the paths for @{term update} and @{term lookup} fork at a certain point. *} theorem lookup_update_other: assumes neq: "y \<noteq> (z::'c)" shows "lookup (update (xs @ z # zs) opt env) (xs @ y # ys) = lookup env (xs @ y # ys)" proof (induct xs arbitrary: env) case Nil show ?case proof (cases env) case Val then show ?thesis by simp next case Env show ?thesis proof (cases zs) case Nil with neq Env show ?thesis by simp next case Cons with neq Env show ?thesis by simp qed qed next case (Cons x xs) note hyp = Cons.hyps show ?case proof (cases env) case Val then show ?thesis by simp next case (Env y es) show ?thesis proof (cases xs) case Nil show ?thesis proof (cases "es x") case None with Env Nil show ?thesis by simp next case Some with neq hyp and Env Nil show ?thesis by simp qed next case (Cons x' xs') show ?thesis proof (cases "es x") case None with Env Cons show ?thesis by simp next case Some with neq hyp and Env Cons show ?thesis by simp qed qed qed qed subsection {* Code generation *} lemma [code, code del]: "(HOL.equal :: (_, _, _) env \<Rightarrow> _) = HOL.equal" .. lemma equal_env_code [code]: fixes x y :: "'a\<Colon>equal" and f g :: "'c\<Colon>{equal, finite} \<Rightarrow> ('b\<Colon>equal, 'a, 'c) env option" shows "HOL.equal (Env x f) (Env y g) \<longleftrightarrow> HOL.equal x y \<and> (\<forall>z \<in> UNIV. case f z of None \<Rightarrow> (case g z of None \<Rightarrow> True | Some _ \<Rightarrow> False) | Some a \<Rightarrow> (case g z of None \<Rightarrow> False | Some b \<Rightarrow> HOL.equal a b))" (is ?env) and "HOL.equal (Val a) (Val b) \<longleftrightarrow> HOL.equal a b" and "HOL.equal (Val a) (Env y g) \<longleftrightarrow> False" and "HOL.equal (Env x f) (Val b) \<longleftrightarrow> False" proof (unfold equal) have "f = g \<longleftrightarrow> (\<forall>z. case f z of None \<Rightarrow> (case g z of None \<Rightarrow> True | Some _ \<Rightarrow> False) | Some a \<Rightarrow> (case g z of None \<Rightarrow> False | Some b \<Rightarrow> a = b))" (is "?lhs = ?rhs") proof assume ?lhs then show ?rhs by (auto split: option.splits) next assume ?rhs (is "\<forall>z. ?prop z") show ?lhs proof fix z from `?rhs` have "?prop z" .. then show "f z = g z" by (auto split: option.splits) qed qed then show "Env x f = Env y g \<longleftrightarrow> x = y \<and> (\<forall>z\<in>UNIV. case f z of None \<Rightarrow> (case g z of None \<Rightarrow> True | Some _ \<Rightarrow> False) | Some a \<Rightarrow> (case g z of None \<Rightarrow> False | Some b \<Rightarrow> a = b))" by simp qed simp_all lemma [code nbe]: "HOL.equal (x :: (_, _, _) env) x \<longleftrightarrow> True" by (fact equal_refl) lemma [code, code del]: "(Code_Evaluation.term_of :: ('a::{term_of, type}, 'b::{term_of, type}, 'c::{term_of, type}) env \<Rightarrow> term) = Code_Evaluation.term_of" .. end